(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2022)
He mentioned in this article the main types of corruption, which are political, moral, financial and administrative. Others may add other types of corruption, such as religious, scientific, media, informational and statistical corruption. At the global level, the focus is largely on financial corruption, although other types of corruption are no less bad than it. Financial corruption can be defined as all financial deviations in violation of general laws or the provisions of regulations, legislation, and procedures regulating the work of the state, private institutions and individuals and applied in state institutions and the private sector in general and inconsistent with the controls and instructions of financial control. In the first part of this study, we drew a conceptual framework for corruption which is distorted social justice and social stability and we gave experienced examples related to this subject. In the second part, the definition, types, actors and prevention of accounting fraud which is pave the way for corruption was mentioned. Besides, we have completed our work by providing examples which is related to accounting fraud.